ANALISIS SENTIMEN MASYARAKAT INDONESIA TERHADAP SEA GAMES 2023 DI TWITTER DENGAN METODE NAÏVE BAYES - Dewi Sekar Arum; Sufajar Butsianto; Retno Fitri Astuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study aims to analyze the sentiment of Indonesian society towards SEA Games 2023 on the Twitter platform using the Naïve Bayes method. Data from Twitter users' responses related to SEA Games were collected and sentiment analysis was performed to identify positive, negative, and neutral responses. The analysis results showed that the majority of responses were positive (33.4%), followed by neutral responses (59.1%) and negative responses (7.5%). The Naïve Bayes method was used to classify sentiment by dividing the data into training and testing sets in different ratio comparisons. The performance of the algorithm was evaluated based on accuracy, precision, and recall. The testing results showed that the 40:60 ratio had the highest accuracy (92.70%). The most frequently occurring words in positive responses were